Penerapan Metode SAS (Struktural Analitiksintetik) untuk Mengatasi Kesulitan Membacapada Siswa Kelas I MI Ma’arif Jatimulyo - Oktafiani Shandra Dewi; Imam Subarkah; Atim Rinawati (Tarbi: Jurnal Ilmiah Mahasiswa, 2022)
The study aims to find out how the use of the SAS (Synthetic Analytical Structural) method toovercome reading difficulties in class I students of MI Ma'arif Jatimulyo. This study uses aqualitative approach by processing the data obtained in the field. The research instrumentused is to use data collection techniques through observation, interviews, documentation, andperform data analysis with data reduction, data presentation and then draw conclusions. Theresults showed that the use of the SAS (Synthetic Analytic Structural) method was appliedduring the learning process, especially in Indonesian subjects, by preparing a lesson plan inthe form of lesson plans in which there were learning objectives, indicators to be achieved,learning methods, and learning media. The lesson plan is prepared in earnest so that thelearning objectives can be achieved properly. The SAS (Synthetic Analytical Structural)method is proven to be able to overcome reading difficulties in class I students at MI Ma'arifJatimulyo